Government Bonds and their Investors : What Are the Facts and Do they Matter? - Andritzky, Jochen (Washington, D.C. : International Monetary Fund, 2012)
This paper introduces a new dataset on the composition of the investor base for government securities in the G20 advanced economies and the euro area. During the last decades, investors from abroad have increased their presence in government bond markets. The financial crisis broke this trend. Domestic financial institutions allocated a larger share of government securities in their portfolios, as Japan has done since its crisis in the 1990s. Increases in the share held by institutional investors or non-residents by 10 percentage points are associated with a reduction in yields by about 25 or 40 basis points, respectively. The data show a varied lead-lag relationship between bond yields and investor holdings. Portfolio balance estimates suggest that a change in statutory or regulatory holdings of government securities to the tune of 10 percent of the outstanding stock causes expected returns to decline by 7 to 25 basis points.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet